A study of lexical availability associated with the areas of learning and motivation for learning - Zambrano, Carolina (2023)
A study of lexical availability for the concepts of learning and learning motivation in student teachers is presented. To this end, the objectives are the following: i) to quantify the available lexicon using the NPD, XR, IC and IDL indexes, ii) to analyze the available lexicon using graphs, and iii) to categorize the available lexicon by means of semantic-cognitive associations. A mixed design methodology integrating quantitative and qualitative analysis was used. The results show that there is a need to improve the vocabulary on learning. Likewise, as a result we present a conceptual scheme of categorizations, which for the learning center of interest is composed of the following categories: reproductive study strategies, study strategies oriented to the application of knowledge, actors of the educational system, spaces of the educational system, elements for teaching-learning. For the motivation for learning center of interest, the categories are goal motivation, vocational orientation, and elements for teaching-learning.